Moral and political obligations in a pandemic - Giubilini, A (Oxford University Press, 2024)
A pandemic changes our moral and political obligations, because it requires us to act differently to meet some of the same standards of harm minimization that we have in normal times. Such changes in moral and political obligations bring about ethical and political disagreements that are often less salient in normal times. However, this disagreement typically arises against a background of widely shared ethical and political values that are relevant to public health – such as harm prevention, solidarity, fairness, a principle of easy rescue, the idea of collective responsibilities. Those values also include a shared sense of proportionality in the way such principles are balanced against self-interest and other personal values. The way in which proportionality applies to those values and principles is, ultimately, what a pandemic calls into question, revealing differences in the way our ethical and political views shape the way those values and principles are specified and qualified.